Undenatured type II collagen prevents and treats osteoarthritis and motor function degradation in T2DM patients and db/db mice. Issue 10 (23rd April 2021) - Rui, Fan; Jiawei, Kang; Yuntao, Hao; Xinran, Liu; Jiani, Hu; Ruixue, Mao; Rui, Liu; Na, Zhu; Meihong, Xu; Yong, Li
Abstract : Osteoarthritis (OA) has been scarcely researched among patients with diabetes mellitus. UC II could prevents and treats osteoarthritis and motor function degradation in T2DM patients and db/db mice. Abstract : Osteoarthritis (OA) has been scarcely researched among patients with diabetes mellitus. This study aims to confirm the preventive and therapeutic effects of undenatured type II collagen (UC II) on OA in aging db/db mice and in patients with T2DM. Firstly, aging db/db mice were randomly assigned to three groups: the UC II intervention (UC II) group, old model (OM) group and positive control group. Meanwhile db/m mice and young db/db mice were used as the normal control and young control groups, respectively. Secondly, fifty-five T2DM patients diagnosed with knee OA were randomly assigned to two groups: UC-II and placebo control groups. After a three-month intervention in both mice and T2DM patients, the subjects' gait and physical activities were assessed and the serum biomarkers including inflammatory cytokines, oxidative stress factors and matrix metalloproteinases (MMPs) were measured. Compared with the OM group mice, those in the UC II group showed a significantly greater superiority in terms of motor functions including the movement trajectories area (163.25 ± 20.3 vs. 78.52 ± 20.14 cm 2 ), the tremor index (0.42 vs. 1.23), standing time (left hind: 0.089 ± 0.03 vs. 0.136 ± 0.04 s), swing (right front: 0.12 ± 0.02 vs. 0.216 ± 0.02 s), stride length (right hind: 7.2 ± 0.9 vs. 5.7 ± 1.1 cm), step cycle (right hind: 0.252 ± 0.05 vs. 0.478 ± 0.11 s) and cadence (14.12 ± 2.7 vs. 7.35 ± 4.4 steps per s). In addition, the levels of IL-4, IL-10, CTX- II and TGF-β in the UC II group were 1.74, 2.23, 1.67 and 1.84 times higher than those in the OM group, respectively, while the levels of MMP-3 and MMP-13 in the UC II group were half those in the OM group. Correspondingly, UC II intervention significantly decreased the scores of pain, stiffness and physical function ( p < 0.05), whereas the 6 MWT and total MET distances in the UC II group increased remarkably ( p < 0.05). After a three-month period of intervention, the varus angle significantly decreased from 4.6 ± 2.0° to 3.0 ± 1.4° and the knee flexion range obviously increased from 57.9 ± 14.0° to 66.9 ± 10.4°. Importantly, the declining trend in the levels of hs-CRP and MDA and the incremental trend in the SOD level were consistent in the db/db mice and OA patients following UC II administration.